A Theoretical review on the importance of Threat Intelligence Sharing & The challenges intricated - et.al, Sandhya Sukhabogi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cyber Threat Intelligence (CTI) is the emerging strategy of cyber defense which helps organizations to combat the latest and more sophisticated cyber threats. Gathering this threat information, analyzing and communicating it between the security teams is very difficult and challenging because of the heterogeneous aspects involved. The necessity of sharing the intelligence related data collected by organizations is increasing day by day to counter the ever changing and highly dynamic threat landscape. In this paper an attempt is made to understand CTI concept and how it is collected and analyzed to form useful actionable intelligence are observed. The importance of Threat intelligence sharing, and various standards working in the area of TIS are also mentioned. Finally the primary challenges in TIS are given a light in a broad view